2018
DOI: 10.1161/jaha.117.008069
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Isolation and Outcomes in Patients With Heart Failure

Abstract: BackgroundPerceived social isolation has been shown to have a negative impact on health outcomes, particularly among older adults. However, these relationships have not been fully examined among patients with heart failure.Methods and ResultsResidents from 11 southeast Minnesota counties with a first‐ever International Classification of Diseases, Ninth Revision (ICD‐9) code 428 for heart failure between January 1, 2013, and March 31, 2015 (N=3867), were prospectively surveyed to measure perceived social isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 27 publications
3
85
2
4
Order By: Relevance
“…There was also evidence of increased risk for socially isolated patients, indicated by significant associations between both living alone and being unpartnered with depression at late convalescence, as well as through the decision tree analysis. Again this is consistent with earlier research that has demonstrated that social isolation is associated with poor mental health including depression and suicide (Cheok et al, 2003;Iliffe et al, 2007;Manemann et al, 2018). Similarly, lack of marital support has been shown to significant predict adverse outcomes (Compare et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…There was also evidence of increased risk for socially isolated patients, indicated by significant associations between both living alone and being unpartnered with depression at late convalescence, as well as through the decision tree analysis. Again this is consistent with earlier research that has demonstrated that social isolation is associated with poor mental health including depression and suicide (Cheok et al, 2003;Iliffe et al, 2007;Manemann et al, 2018). Similarly, lack of marital support has been shown to significant predict adverse outcomes (Compare et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“… 50 In patients with heart failure, higher perceived loneliness was associated with more frequent ambulatory and emergency room visits and hospital admissions. 51 Vascular pathology and morbidity associated with SI/L are likely to contribute to the onset and disease course of other late-life conditions such as geriatric depression and neurocognitive disorders.…”
Section: Definitionsmentioning
confidence: 99%
“…The evaluation of the social status of each AHF patient is therefore important for preventing re-admission due to HF and a poor prognosis. Several groups have systemically investigated the impact of social determinants or isolation on the prognosis of AHF patients (4-7). Lu et al reported that the marital status and living conditions were correlated with the mortality and readmission rate among African Americans with HF (5).…”
Section: Introductionmentioning
confidence: 99%